1999
DOI: 10.1042/bj3400505
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a palmitoylatable band 3-binding domain of human erythrocyte membrane protein 4.2

Abstract: Evidence accumulated over the years suggests that human erythrocyte membrane protein 4.2 is one of the proteins involved in strengthening the cytoskeleton-membrane interactions in the red blood cell. Deficiency of protein 4.2 is linked with a variety of hereditary haemolytic anaemia. However, the interactions of protein 4.2 with other proteins of the erythrocyte membrane remain poorly understood. The major membrane-binding site for protein 4.2 resides on the cytoplasmic domain of band 3 (CDB3). In order to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Some interactions between cell surface and skeletal proteins of RBCs have been characterized in detail. For instance, the N‐terminal domain of Band 3 associates with ankyrin, protein 4·1 and protein 4·2, and the interacting domains of each protein have been mapped to some extent (Tanner, 1993; Lux & Palek, 1995 for reviews; Rybicki et al , 1995; Bhattacharyya et al , 1999). It has also been shown that the cytoplasmic tail of GPC, protein 4·1 and protein p55 form a ternary complex that is critical for membrane stability and the protein domains that interact have been precisely delineated (Nunomura et al , 2000).…”
mentioning
confidence: 99%
“…Some interactions between cell surface and skeletal proteins of RBCs have been characterized in detail. For instance, the N‐terminal domain of Band 3 associates with ankyrin, protein 4·1 and protein 4·2, and the interacting domains of each protein have been mapped to some extent (Tanner, 1993; Lux & Palek, 1995 for reviews; Rybicki et al , 1995; Bhattacharyya et al , 1999). It has also been shown that the cytoplasmic tail of GPC, protein 4·1 and protein p55 form a ternary complex that is critical for membrane stability and the protein domains that interact have been precisely delineated (Nunomura et al , 2000).…”
mentioning
confidence: 99%
“…Protein 4.2 is a member of the TG (transglutaminase) family of enzymes, but has no catalytic activity [12]. It is myristoylated at Gly 2 [13] and palmitoylated at Cys 173 [14], which may allow association with cellular membranes. Protein 4.2 has been shown to associate with the plasma membrane of Sf9 insect cells [15] and Xenopus oocytes [16] in the absence of AE1.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 1 (right-hand panel), a homology model we constructed of protein 4.2 using human TG2 [17] as a template, is placed next to the crystal structure of cdAE1 to show their relative sizes. The N-terminal region of protein 4.2, encompassing residues 1−238, has been shown to represent the cdAE1-binding domain [14]. Residues 157−181 were found to be critical for the interaction and predicted formation of a β-hairpin in the centre of protein 4.2 with Cys 173 located at the bend.…”
Section: Introductionmentioning
confidence: 99%
“…Band 3-protein 4.2-ankyrinspectrin interactions probably stablilize linkages between the cytoskeleton and the overlying membrane. Protein 4.2 associates in itro with band 3 [15,16], ankyrin [16] and spectrin [17]. Human erythrocyte protein 4.2 is N-terminally myristoylated [18] and palmitoylated [19], and its interaction with band 3 is modulated by palmitoylation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Protein 4.2 associates in itro with band 3 [15,16], ankyrin [16] and spectrin [17]. Human erythrocyte protein 4.2 is N-terminally myristoylated [18] and palmitoylated [19], and its interaction with band 3 is modulated by palmitoylation [15]. It can be phosphorylated by a red-cell-membrane kinase that partially co-purifies with it, and has properties similar to the catalytic subunit of cAMP-dependent kinase [20].…”
Section: Introductionmentioning
confidence: 99%